Infection SARS-CoV-2 chez la femme enceinte : profil épidémiologique, clinique, biologique et évolutifs, sur 35 cas au Niveau de l’EHS Mère et Enfant Laghouat et service de Covid EPH Laghouat - MADNI Zineb; BOUDEFFEUR Wassila (Université Amar Telidji de Laghouat Faculté de Médecine, 2022)
Introduction: The recent COVID-19 pandemic has led to an unprecedented global health crisis. The susceptibility of pregnant women to infections has raised many questions about the risk of transmission, the teratogenic risk and maternal-fetal complications. The speed with which the infection progressed, as well as the ambiguity of its impact on pregnancy due to the lack of scientific data, prompted obstetricians to adapt their practice based on pragmatic behavior. We gave interest to this subject declared by the WHO as a global pandemic in early March 2020 to try to plan the obstetric care of patients infected with SARS-CoV-2. Methods: This is a retrospective, descriptive, observational study carried out between 06/01/2020 and 10/31/2021, a period of 16 months relating to cases of COVID-19 during pregnancy, delivery and in the postpartum concerning 35 pregnant patients with covid-19 in LAGHOUAT Results: From the database of our study containing a series of 35 cases whose clinical signs were distributed as follows: 28 patients presented with fever, 80% of cases, 23 patients had myalgia, 66% of the series, 22 patients complained of headaches, 63% of patients, and 11 patients of anosmia, 31% of cases. The respiratory signs were dominated by the cough present in 21 patients or 60% of the cases, followed by sore throat found in 23 patients or 66% of the patients and finally 27 patients were dyspneic or 77% of the series of cases. According to these results and based on current knowledge; This work aims to describe the different possible clinical manifestations in pregnant women and to establish the principles of management in the event of Covid-19 infection as well as other symptoms. 37.1% of imaging will find pathological results. Covid-19 infection in pregnant women will be serious in 7 cases, 20% of cases. The severe forms are mainly encountered during the 3rd trimester of pregnancy. Maternal infection with Covid-19 can have adverse consequences on obstetric outcomes and lead to: Premature delivery in 63% of cases, acute fetal distress in 49%, and preeclampsia in 6% of cases. In our study, the mode of delivery was carried out by cesarean section in 74.3% of cases. It is also plausible that maternal infection with Covid-19 can have harmful consequences on newborns. This can range from clinical signs benign until death. 6% of newborns had an IUGR, 29% had mild clinical signs while 49% had severe clinical signs (with 5 deaths 14%). The majority of newborns had a bad APGAR score. Conclusion: According to these results and based on current knowledge; This work aims to describe the different possible clinical manifestations in pregnant women and to establish the principles of management in the event of COVID-19 infection.
142 p.